Research into the influence OF AL2O3 nanoparticle admixtures on the magnitude of isopropanol molar volume - Zhelezny, Vitaly; Lozovsky, Taras; Gotsulskiy, Vladimir; Lukianov, Nikolai; Motovoy, Igor (Eastern-European Journal of Enterprise Technologies, 2017)
The results obtained in experimental study of density of solutions of isopropyl alcohol and Al2O3 nanoparticles are given. Studies on nanofluid density were carried out using pycnometric method in a temperature range from 250 K to 315 K at weight concentrations of nanoparticles 0.92 %, 1.81 %, 4.01 % and 6.65 %. The obtained data made it possible to reveal temperature and concentration dependences of the studied nanofluids and calculate magnitude of the excess molar volume as well as hydrodynamic diameter of nanoparticles. The data on the value of hydrodynamic diameter obtained from the information on excess molar volume were in good agreement with the data measured by the method of dynamic light scattering. It was shown that the equivalent diameter of the adsorption layer of isopropanol molecules on nanoparticles decreases with an increase in concentration of Al2O3 nanoparticles. Based on these studies, a new method for predicting molar volume of nanofluids was proposed. This technique takes into account presence of a sorbed layer of base fluid molecules on the nanoparticle surface. As the studies show, density of the sorption phase is higher than density of isopropyl alcohol at the set-up parameters. Presence of a sorption layer of isopropyl alcohol molecules on the nanoparticle surface determines magnitude of the excess molar volume. This fact has to be taken into account when simulating density of nanofluids. A simple method was also proposed for determining equivalent diameter of the adsorbed layer of base fluid molecules on the nanoparticle surface. The essence of the method is an assumption that nanoparticles have a shape close to spherical and the surface layer is a spherical layer of sorbed isopropanol molecules on the nanoparticle. This method allows determination of the equivalent diameter from easily measured data. It is recommended for use in modeling viscosity, thermal conductivity and heat capacity of nanofluids. It is also recommended for use in development of heat exchange models for power equipment.